Cloning and characterization of a novel Nicotiana tabacum ABC transporter involved in shoot branching. Issue 2 (7th October 2014) - Xie, Xiaodong; Wang, Genhong; Yang, Ling; Cheng, Tingcai; Gao, Junping; Wu, Yuqian; Xia, Qingyou
<x xml:space="preserve">Abstract</x> The ATP‐binding cassette (ABC) superfamily is a large protein family with diverse physiological functions in all kingdoms of life. One distinguished subfamily, the pleiotropic drug resistance (PDR) transporters, has only been identified in plants and fungi. Here, we identified a Nicotiana tabacum PDR gene, NtPDR6, which is a homolog of Petunia hybrida PDR1. The full‐length cDNA of NtPDR6 had a 4482‐bp open reading frame encoding a full‐size ABC transporter with 1493 amino acids. Sequence comparison showed that NtPDR6 had high homology with plant PDR proteins. NtPDR6 was strongly induced by phosphate starvation as well as by 1‐naphthalene acetic acid. Tissue expression pattern analysis showed that NtPDR6 was detected in all surveyed tissues but preferentially in roots. We cloned the 1.3‐kb NtPDR6 promoter and found that there was one phosphate starvation response‐related element Pho‐like and several root‐specific expression‐related elements rootmotiftapox1 in the NtPDR6 promoter. A tissue‐specific pattern of NtPDR6 promoter‐β‐glucuronidase expression was dominantly observed in subepidermal cells and the elongation zone of lateral roots. RNA interference technology was used to knock down NtPDR6 expression, and there was a significantly increased branching phenotype in the NtPDR6 knockdown plants. These data suggest that NtPDR6 plays a key role in regulation of shoot branching processes.